Emissions of sulphur, nitrogen and alkaline particles in Sweden 1900-1990 - "Kindbom, K"; "Sjoeberg, K"; "Loevblad, G [Swedish Environmental Research Inst., IVL, Goeteborg (Sweden)]" (1995)
In order to develop models to predict the fate of acidified ecosystems in the future, it is necessary to have knowledge about the development of the processes in the past. Sulphur has historically been the most important pollutant influencing acidification, but nitrogen has contributed as well. The acidification process is counteracted by the deposition of alkaline particles and by weathering of rock. Basic information needed in order to map acid deposition is both the amount of emissions as well as the geographical localization of the sources in combination with meteorology and dispersal processes for sulphur, nitrogen and base-cations. In the present work the emissions to the atmosphere of sulphur dioxide, nitrogen oxides, ammonia and alkaline particles in Sweden during 1900-1990 were investigated. The aim of the work was to estimate the accumulated acid deposition from the atmosphere to the ecosystems during this period of time. Emissions from energy production and industrial processes, as well as from traffic and animal husbandry (cattle manure) were included. The historical estimates were of necessity rather rough in some parts since no emission measurements were made and the knowledge on processes in the beginning of the century was not documented. The work is subdivided into the emission inventory, presented here, and the modelling of depositions, which will be presented later. (orig.)
Keywords: "54 ENVIRONMENTAL SCIENCES"; "AIR POLLUTION"; "NITROGEN OXIDES"; "SULFUR DIOXIDE"; "AMMONIA"; "DUSTS"; "SWEDEN"; "SULFUR"